Modelling tillering of annual grasses as a function of plant density: Application to Sahelian rangelands productivity and dynamics - Hiernaux, Pierre H.Y.; Leeuw, P.N. de; Diarra, L. (Elsevier, 1994)
Plant density and tiller cunts were done in several Sahelian rangelands in Mali, under a variety of soil, rainfall and grazing situations. Numeric models were developed to explain the dynamic relationship between grass tillering and herb density. Tests of application of these models to the plant and tillering density data justify the selection of the Maxima function model. Discussion of the results leads to an ecological interpretation of the parameters of the model which relate the dynamics of tillering to the concepts of ecological niche and inter-plant competition for resources. The application of the model helps in assessing the role of grass tillering in the structure and productivity of Sahelian rangelands and in their response to drought and pastoral management changes.